SUATU PENDEKATAN SEMIKLASIK UNTUK KOEFISIEN DIFUSI DIRI GAS - Sutrisna
Through simplification of the semiclassical BBGKY hierrarchy valued as f3 = 0, the semiclassical be drown for the binery Collisions. This equation is accomplished by Chapman-Enskog perturbation method, which formulates the self difusion coefficient of semiclassic